Social Management of Development: the Challenge of Articulating Social Actors in Territories of Citizenship Program in the North Region of Rio de Janeiro State - Zani, Felipe Barbosa; Tenório, Fernando Guilherme (Organizações & Sociedade, 2014)
This study analyzes how far the design and implementation of the Programa Territórios da Cidadania in the North Region of Rio de Janeiro State increase pluralism, especially including business representatives. It was realized semi-structured interviews, which were complemented by a documentary analysis and treated by analysis of content with combined graph developed based on the habermasian concept of deliberative citizenship. The design of this policy indicates hesitant incentive to include businessmen, such that specific politic aspects of intersectorial partnership are briefly pointed out. Besides that, the processes of territory construction valorizes the family farming; the civil society groups rejects to include businessmen in territorial collegiate body; and the analysis process of territorial projects encumbers the propose of innovate projects articulated with businessmen. In conclusion, the social management experience analyzed was not capable to promote the concertation of dynamic social forces presents in the territory.